Output optimization of biodegradable triboelectric nanogenerators. (1st December 2022) - Lyu, Yang; Wang, Yi
Abstract: The emergence of nanogenerators provides a creative way of collecting tiny energy. Biodegradable triboelectric nanogenerators (BD-TENGs) have become a hot topic in the field of green energy due to their eco-friendliness, safety, and good biocompatibility. The biggest problem in the development of BD-TENGs is how to improve their relatively low output performance. Based on major factors that have a significant impact on the power generating process during friction, including the triboelectric polarity of friction layers, frictional contact areas between them, and their charge accumulation ability, various methods to improve the output performance of BD-TENGs were developed. This review summarizes the existing optimizing methods of BD-TENGs, which can be generally divided into three groups, including the alteration of friction material compositions, the change of surface microstructures, and the promotion of dielectric properties, thus aiming at providing some ideas for future research in the field of BD-TENG. Graphical Abstract: This review summarizes the approaches to improve the electrical output performances of biodegradable triboelectric nanogenerators (TENGs). The approaches can be classified into three main groups according to the affecting factors of TENGs, respectively the triboelectric properties, the surface structures, and the dielectric properties. ga1 Highlights: The low output performance of BD-TENG limits its application. The output of TENG relies on its composition, surface morphology, and permittivity. Composition adjustment and chemical modification lift the triboelectric polarity. Surface patterning enhances the triboelectric efficiency. Improvement of permittivity and polarization helps charge storage.